A Descriptive Study On Teaching Speaking At The FirstSemester Of Economy Faculty Of Muhammadiyah University Of Surakarta - Purnawan, Yoga, Drs. Djoko Srijono, M.Hum, Rini Fatmawati M.Hum (2013)
This research aims at describing teaching speaking to the first semester of economy faculty Muhammadiyah university of surakarta 2012/2013 academic year. The objectives of this research paper are to describe: 1) process of teaching speaking on the first semester of economy faculty Muhammadiyah university of surakarta, 2) the method that used the teacher in teaching speaking. The type of this research is descriptive qualitative. The data of this research are collected by observing the English class and interviewing the English teacher. The data of this research are the first year student's activities in speaking in Economy faculty UMS in 2012/2013 academic year, field note and data from interviewing English teacher. The subject of this research is English teacher and the firs year students of economy faculty UMS. The object of this research is teaching speaking to the firs year students of economy faculty UMS. The methods of collecting the data of the research are observation, interview, and documents. Based on the result of the analysis, the teacher uses BKOF, MOT, JCOT, ICOT as the learning procedure. The objective of teaching speaking is to develop the communicative competence of the students in speaking skills. The materials are students worksheet and real situation. The media are picture, realia, tape and LCD projector. The techniques are role playing, pair work and discussion, game, problem solving. The evaluation is conducted by interpreting all of English skills. While the teacher roles are facilitator, counselor, source information, and motivator. The methods that used by the teacher are natural approach, direct method, audio-lingual method.